Feasibility study on using combined tomography and spectroscopy techniques to evaluate the physical and chemical characteristics of organo-mineral fertilisers - Sakrabani, Ruben; Mosca, Sara; Liptak, Alexander; Burca, Genoveva (Frontiers, 2025)
Fertilisers play a key role in agriculture, providing key nutrients needed by crops to ensure a secure food supply. However, with increasing prices and rising environmental concerns, there is a growing need to rely on alternative and sustainable fertiliser sources, introducing the opportunity to use organic amendments to formulate organo-mineral fertilisers (OMF). Despite their environmental advantages, the inherent variability in composition of organic amendments within OMF poses a challenge for their standardization. This study aims to use OMF derived from anaerobic digestate and coupled with carbon capture technologies to analyze for its physical characteristics and chemical composition using neutron computed tomography (NCT), X-ray computed tomography (XCT) and Raman spectroscopy (RS). This is a feasibility study to assess using non-destructive techniques on OMF as previously this has not been explored. This work represents the first attempt to utilize a combination of imaging techniques to investigate on OMF and demonstrates their feasibility for measuring the variability between individual samples. This is a proof-of-concept study which shows that combining NCT and XCT can provide images on how uniformly packed each OMF pellet are. The use of RS is to characterize OMF is more challenging largely due to the high fluorescence background arising from its matrix. This study needs to be further developed to enable image-based analysis using machine learning algorithms to determine characteristics of large batches of OMF. Further development is needed building on this work to quantify OMF pellet characteristics so that it can be confidently used as novel fertilisers in agriculture.
Keywords: 3002 Agriculture, Land and Farm Management; 30 Agricultural, Veterinary and Food Sciences; 41 Environmental Sciences; 2 Zero Hunger; 30 Agricultural, veterinary and food sciences; 41 Environmental sciences; organo-mineral fertilisers; soil nutrients; neutron computed tomography; Raman spectroscopy; X-ray computed tomography